Does Market Timing Drive Capital Structure? Empirical Evidence from an Emerging Market - Çelik, Sibel; Akarim, Yasemin Deniz (International Journal of Economics and Financial Issues, 2012)
The purpose of this study is to test how equity market timing affects capital structure from the perspective of IPO (Initial Public Offering) event in ISE for the period between 1999-2008. Our dataset comprises of all firms (75 firms) that went public from the period of January 1999 to December 2008 in Turkey that are available in ISE database. We analyse the market timing theory by applying cross sectional regression method. For this purpose, first, we test the impact of market timing on the amount of equity issued by IPO firms. Second we examine the impact of market timing on capital structure. We conclude that market timing theory is not valid for Turkey. Keywords: Capital Structure; Market Timing; IPO; Turkey JEL Classifications: G30; G32